Impact of isolated dissolved organic fractions from seawater on biofouling in reverse osmosis (RO) desalination process - Yin, Wenqiang (2021)
The biofouling potential of three isolated dissolved organic fractions from seawater according to their molecular weights (MWs), namely, fractions of biopolymers (F.BP, MW > 1000 Da), humic substances and building blocks (F.HS&BB, MW 350-1000 Da), and low molecular weight compounds (F.LMW, MW < 350 Da) were characterized by assimilable organic carbon (AOC) content. The AOC/DOC ratio was in the order of F.LMW (∼35%) > F.BP (∼19%) > F.HS&BB (∼8%); AOC/DOC of seawater was ∼20%; organic compositions of seawater were BP ∼6%, HS&BB ∼52% and LMW ∼42%; LMW accounted for >70% of AOC in seawater. Their impact on SWRO biofouling in term of flux decline rate was in the order of F. LMW (∼30%) > F.BP (∼20%) > F.HS&BB (<10%). Despite being the major organic compound in seawater, HS&BB showed marginal effect on biofouling. The role of indigenous BP was less critical owing to its relatively low concentration. LMW, which was the major AOC contributor, played a significant role in biofouling by promoting microbial growth that contributed to the build-up of soluble microbial products and exopolymeric substances (i.e., in particular BP). Therefore, seawater pretreatment shall focus on the removal of AOC (i.e., LMW) rather than the removal of biopolymer.